Propuesta de renovación urbano sectorial del predio del aeropuerto Benito Salas (Neiva– Huila) (2020)
This investigation begins based on the problems and affectations generated by the current location of the airport of the city of Neiva, which is interfering with the proper development of the municipality, normally the airports are on the outskirts of the cities, while this is immersed within the urban area, generating road conflicts and low urban development.